Moral Hazard and Fiscal Gambling : An Analysis of Radical Tax Aggressiveness as a Survival Strategy in Multinational Corporations Facing Terminal Distress - Aldi Adi Pratama; Muhammad Azzmi; Rakha Ramadhana A.B. (UANG: Journal of Fiscal and Monetary Studies, 2025)
During the period of global economic turmoil from 2020 to 2025, tax avoidance fundamentally transformed from a routine cost-efficiency effort into a vital element for corporate survival. For multinational corporations (MNCs) facing terminal distress, tax management often shifts toward fiscal gambling, where extreme tax aggressiveness is utilized to instantly secure internal liquidity and meet urgent short-term obligations. This research aims to analyze the shift in corporate tax strategies in response to debt market tightening and to identify the trade-off between instant cash savings and the inflated cost of capital resulting from information opacity. Employing a descriptive-analytical qualitative approach, the study positions financial metrics specifically ETR, CETR, BTD, and DTAX as signals of strategic managerial behavior reflecting the tension between fiscal obligations and survival. The results reveal that in emergency situations, supervisory boards may consciously endorse radical tax strategies as part of a restructuring plan to save the company from insolvency, reflecting a manifestation of moral hazard where short-term survival is prioritized over sustainable compliance. However, the study concludes that global regulatory frameworks, such as the OECD’s Pillar Two global minimum tax and digital fiscal monitoring, are increasingly constricting the latitude for such aggressive maneuvers. Ultimately, while these desperate maneuvers attempt to forestall insolvency, they often create a "vicious cycle" of heightened legal exposure and the erosion of market confidence, making transparent compliance an existential necessity for MNCs aiming to endure from 2025 onward.